2011
DOI: 10.1016/j.ejcts.2011.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of lung cancer in smokers with light and mild chronic obstructive pulmonary disease: a retrospective analysis of Japanese surgical cases

Abstract: We concluded from our analysis that COPD-related LC may have a higher malignant potential than LC in non-COPD smokers, as the histological differentiation grade and clinical outcomes were poorer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
10

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(45 citation statements)
references
References 14 publications
1
34
0
10
Order By: Relevance
“…After initial screening based on titles and abstracts with predefined inclusion/exclusion criteria, 58 articles were identified for full-text review, of which 26 articles were identified for metaanalysis. 3,5,[13][14][15][16][17][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Of these, 19 specifically reported the results on COPD, 3,5,13,14,16,20,[22][23][24]27,29,30,32-38 5 on emphysema, 17,21,26,28,31 and 2 on both COPD and emphysema 15,25 with lung cancer prognosis. Table 1 presents the characteristics of 21 studies for concomitant COPD and lung cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…After initial screening based on titles and abstracts with predefined inclusion/exclusion criteria, 58 articles were identified for full-text review, of which 26 articles were identified for metaanalysis. 3,5,[13][14][15][16][17][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Of these, 19 specifically reported the results on COPD, 3,5,13,14,16,20,[22][23][24]27,29,30,32-38 5 on emphysema, 17,21,26,28,31 and 2 on both COPD and emphysema 15,25 with lung cancer prognosis. Table 1 presents the characteristics of 21 studies for concomitant COPD and lung cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…The Global Initiative for Chronic Obstructive Lung Disease (GOLD) guidelines recommend that spirometry should be performed after administration of a short‐acting inhaled bronchodilator to minimize variability such as asthma; however most medical records documented that spirometry had been performed without an inhaled bronchodilator in a practice setting. Patients with a smoking history and a ratio of forced expiratory volume in one second (FEV1) to forced vital capacity of less than 70% were classified as COPD patients . GOLD spirometry grades were used to classify the severity of airflow limitation: GOLD 1 (mild), FEV1 ≥ 80% predicted; GOLD 2 (moderate), 50% ≤ FEV1 < 80% predicted; GOLD 3 (severe), 30% ≤ FEV1 < 50% predicted; and GOLD 4 (very severe), FEV1 < 30% predicted .…”
Section: Methodsmentioning
confidence: 99%
“…COPD was defined as FEV 1 /FVC <0.7 (FVC, forced vital capacity) with a smoking history. 2,11) GOLD spirometric grades were used to classify the severity of airflow limitation: GOLD 1 (mild), FEV 1 ≥80% predicted; GOLD 2 (moderate), 50% ≤FEV 1 <80% predicted; GOLD 3 (severe), 30% ≤FEV 1 <50% predicted; and GOLD 4 (very severe), FEV 1 <30% predicted [2]. Patients who had never smoked and smokers without COPD were designated as non-COPD group.…”
Section: Definitionsmentioning
confidence: 99%